Study on the application of a segmented sodium citrate solution anticoagulation strategy in critically ill patients receiving CRRT: a prospective, randomized controlled study - Yu Chen; Fang Feng; Hong Guo; Lu Zhang; Jian Liu (Trials, 2024)
Abstract Background To explore the feasibility and effectiveness of a segmented sodium citrate solution anticoagulation strategy in patients receiving CRRT. Methods A prospective, randomized controlled study was conducted. Results According to the inclusion and exclusion criteria, 80 patients were included and randomly divided into two groups. Moreover, coagulation indices, liver function indices, renal function indices, and SOFA and APACHE II scores did not significantly differ between the two groups (P > 0.05). The coagulation grade of the venous ports in the experimental group was lower than that in the control group and the two groups of filters, but the difference was not statistically significant (P = 0.337). Both sodium citrate solution infusion methods maintained a low blood calcium concentration (0.25–0.45 mmol/L) in the peripheral circulation pathway, and no patient developed hypocalcaemia (< 1.0 mmol/L). The lifespans of the extracorporeal circulation tube in the experimental group and the control group were 69.43 ± 1.49 h and 49.39 ± 2.44 h, respectively (t = 13.316, P = 0.001). Conclusion The segmented citrate solution anticoagulation strategy could extend the lifespan of the extracorporeal circulation tube and improve CRRT efficacy. Trial registration The Chinese Clinical Trial Registry number is ChiCTR2200057272. Registered on March 5, 2022.